Component revision identification based on IDL - Brada, Přemysl (Software engineering notes.)
Although software components have become one of the mainstream technologies, they still lack a supportive versioning scheme. This paper describes a system for revision identification of released components with well defined semantics. It is based on the analysis of changes in the component IDL or ADL specification structured into a hierarchy of traits and categories of declarations.